Pendampingan Integrasi Intellectual Capital bagi Pengembangan Kapasitas SDM pada Tim Usaha Perempuan Berbasis Kearifan Lokal - Rosiana, Auliya; Indraswari, Nurul Myristica; Purnamarini, Tri Ratna (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2026)
This community service activity aims to integrate intellectual capital into the development of human resource capacity within the local wisdom based handicraft business team of the DAWIS Asoka Women’s Economic Empowerment Group in Dusun Dondong, Tegaltirto, Berbah, Sleman. The program focuses on strengthening human capital, structural capital, and relational capital through training and mentoring on the utilization of pipe cleaners as raw materials for economically valuable handicraft products. The implementation method consists of preparation, training, mentoring, and evaluation stages. The results indicate improvements in the knowledge, skills, and creativity of group members in producing handicraft products such as decorative flowers and ornaments based on local wisdom. This activity contributes to women’s economic empowerment while supporting the preservation of local wisdom through the development of community- based handicraft enterprises.